Konflik Batin Lansia Pascakematian Pasangan Hidup sebagai Inspirasi Penciptaan Skenario Kar - Nur Sayyidah; Elara Karla Nugraeni; Kurnia Rahmad Dhani (Institut Seni Indonesia Yogyakarta, 2025)
Studi penciptaan karya ini berangkat dari pengalaman empiris penulis mengenai pergulatan batin neneknya setelah kehilangan suami, yang terkait dengan fenomena late-life crisis dan grief dream. Penciptaan skenario film menggunakan pendekatan empiris (observasi dan wawancara) yang diolah dengan struktur naratif miniplot Robert McKee. Teori eksistensialisme Sartre (konsep l'autre) dan pendekatan estetika realisme magis diintegrasikan untuk membangun konflik dan kedalaman karakter. Hasil penelitian penciptaan ini menunjukkan bahwa pengalaman empiris lansia yang berduka dapat diolah dengan apik menjadi narasi sinematik yang kaya makna, merepresentasikan kompleksitas emosi, pencarian makna, dan proses penyembuhan psikologis lansia. Skenario Kar tidak hanya menjadi refleksi personal, tetapi juga menawarkan perspektif baru mengenai pentingnya dukungan sosial dan pemaknaan ulang identitas bagi lansia pasca kehilangan pasangan. The Inner Conflict of the Elderly in the Aftermath of Spousal Death: A Creative Foundation for the Screenplay KarThis creation study originates from the author's empirical experience of witnessing his grandmother's inner turmoil following the sudden loss of her husband, which is related to the phenomena of late-life crisis and grief dream. The film scenario was developed using an empirical approach (through observation and interviews), which was then processed using Robert McKee's miniplot narrative structure. Sartre's existentialist theory (the concept of the Other) and the aesthetic approach of magical realism are integrated to build character conflict and depth. The results of this creative research demonstrate that the empirical experiences of grieving elderly individuals can be effectively crafted into a meaningful cinematic narrative, representing emotional complexity, the search for meaning, and the process of psychological healing in the elderly. The screenplay Kar not only serves as a personal reflection but also offers a new perspective on the importance of social support and the redefinition of self-identity for the elderly after the loss of a life partner.